Detection of postoperative granulation tissue with an ICG-enhanced integrated OI-/X-ray System - Sutton Elizabeth J; Henning Tobias D; Thullier Daniel; Acosta Frank L; Krug Christian; Boddington Sophie; Meier Reinhard; Tavri Sidhartha; Lotz Jeffrey C; Daldrup-Link Heike E (Journal of Translational Medicine, 2008)
Abstract Background The development of postoperative granulation tissue is one of the main postoperative risks after lumbar spine surgery. This granulation tissue may lead to persistent or new clinical symptoms or complicate a follow up surgery. A sensitive non-invasive imaging technique, that could diagnose this granulation tissue at the bedside, would help to develop appropriate treatments. Thus, the purpose of this study was to establish a fast and economic imaging tool for the diagnosis of granulation tissue after lumbar spine surgery, using a new integrated Optical Imaging (OI)/X-ray imaging system and the FDA-approved fluorescent contrast agent Indocyanine Green (ICG). Methods 12 male Sprague Dawley rats underwent intervertebral disk surgery. Imaging of the operated lumbar spine was done with the integrated OI/X-ray system at 7 and 14 days after surgery. 6 rats served as non-operated controls. OI/X-ray scans of all rats were acquired before and after intravenous injection of the FDA-approved fluorescent dye Indocyanine Green (ICG) at a dose of 1 mg/kg or 10 mg/kg. The fluorescence signal of the paravertebral soft tissues was compared between different groups of rats using Wilcoxon-tests. Lumbar spines and paravertebral soft tissues were further processed with histopathology. Results In both dose groups, ICG provided a significant enhancement of soft tissue in the area of surgery, which corresponded with granulation tissue on histopathology. The peak and time interval of fluorescence enhancement was significantly higher using 10 mg/kg dose of ICG compared to the 1 mg/kg ICG dose. The levels of significance were p < 0.05. Fusion of OI data with X-rays allowed an accurate anatomical localization of the enhancing granulation tissue. Conclusion ICG-enhanced OI is a suitable technique to diagnose granulation tissue after lumbar spine surgery. This new imaging technique may be clinically applicable for postoperative treatment monitoring. It could be also used to evaluate the effect of anti-inflammatory drugs and may even allow evaluations at the bedside with new hand-held OI scanners.